The Prevalence of Vitamin B12 Deficiency in Type 2 Diabetes with Neuropathy; A Multi-Center Study - Khalid Usman, Rab Nawaz Khan, Sahibzada Imtiaz Ahmad, Saleh Ahmad, Kifayat Ali, Tahir Ghafar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Vitamin B12 is essential to nerve-related functionalities and hematopoiesis. There may be neuropathy-like symptoms in case of deficiency as they resemble those caused by diabetic neuropathy. The risk factors involved are patients diagnosed with Type 2 Diabetes Mellitus (T2DM), especially those patients undergoing long term metformin treatment whose absorption abilities have been affected. This deficiency cannot be reversed and it is therefore important to detect it early enough before the damage caused on the nerves is permanent. A wide range of studies have shown that there is a high incidence of B12 deficiency among patients with diabetes, in particular the peripheral neuropathy population, reinforcing the importance of regular screening and possible supplementation. Objective: To determine the prevalence of vitamin B12 deficiency in patients with type 2 diabetes mellitus (T2DM) presenting with neuropathy, and to assess its association with metformin usage and the severity of neuropathy. Study design: A cross-sectional Multi-Center study: Place and duration of study: Department of Endocrinology, MTI-HMC Peshawar; Timergara Teaching Hospital, Timergara and the District Headquarter Hospital, Dir Upper from January 2022 to June 2022. Methods: 100 T2DM patients with clinically established neuropathy. Exclusion was based on chronic alcohol consumption, renal failure and B12 supplement during a short time. Quantification of vitamin B12 was carried out by chemiluminescent immunoassay. Measurement of neuropathy was done by Michigan Neuropathy Screening Instrument. The number of metformin dose and duration were charted. Statistical operation was done through SPSS; p-value 0.05 was to be regarded as significant. Results: Of the 100 patients, 60 per cent were Vitamin B12 deficient (<200 pg./mL). The average patients age was 58.3 9.6 years. The deficiency of B12 in people on metformin longer than 5 years was much more frequent (p = 0.002). The low B12 levels were associated strongly with very high scores of neuropathies (p=0.01). In patients, there was less severe neuropathy among those with normal levels of B12. The prevalence of deficiency did not differ significantly according to gender (p = 0.28). Conclusion: vitamin B12 deficiency is very common in individuals who have T2DM and neuropathy, as well as in individuals who are taking long-term metformin. Screening and early supplementation of Vitamin B12 in diabetic patients can reduce the risk of developing and graduating diabetic neuropathy, thus enhancing quality of life and translate to the issue of disability among diabetic patients. Keywords: Vitamin B12, Type 2 Diabetes, Neuropathy, Metformin